Determinants of Maqasid al-Shari'ah-based performance measurement practices : the case of Malaysian Islamic Banks - Muhammad Ahmar bin Ali (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2014)
Islamic banking has emerged as a thriving industry because demand is increasing in both developed and developing countries including Malaysia. Islamic banks serve Muslim and non-Muslim communities with interest-free financial products and services. The development of Islamic banks should be in tandem with their contributions to achieve the objectives of Islamic law (Maqasid al-Shari'ah). Maqasid al-Shari'ah should form an integral part of the strategies underpinning the development of the Islamic financial system. However, the growth of Islamic banks is being challenged as they are not able to achieve Maqasid al-Shari'ah. It is argued that the failure to achieve Maqasid al-Shari'ah is caused by the weakness of the Performance Measurement System (PMS) of the banks. The key role of a PMS is to provide a link between business strategies and organizational objectives. Thus, the PMS of Islamic banks must be adapted to align with Maqasid al-Shari'ah. This study aims to explore the performance measurement practices in Malaysian Islamic banks based on Maqasid al-Shari'ah. The study also examines the differences between the two types of Islamic bank in Malaysia, namely, full-fledged Islamic banks and Islamic banking subsidiaries, in terms of Maqasid al-Shari'ah-based performance measures and organizational performance. To gather data for this study, the researcher distributed 146 questionnaires to various participants from head officers to senior managers in each department/business unit of all 16 Islamic commercial banks in Malaysia. The results indicate that only technological advancement and regulatory compliance have a direct relationship with the Maqasid al-Shari'ah-based performance measures. In addition, the results also indicate that having Maqasid al Shari'ah-based performance measures would enhance the organizational performance of Islamic banks. The results also reveal that a differentiation strategy, technological advancement, innovativeness, and regulatory compliance bring about greater interdependence on the Maqasid al-Shari'ah-based performance measures, which induces improved organizational performance in Islamic banks. This study also found that financial and non-financial measures as well as performance measures based on the Maqasid al-Shari'ah framework are equally important and are being implemented in Islamic banks in Malaysia. However, the findings show that there are significant differences in terms of Maqasid al-Shari'ah-based performance measures as well as organizational performance for both types of Islamic bank. Therefore, this study contributes to the performance measurement literature on Maqasid al-Shari'ah-based performance measures in the context of Islamic banks